МОДЕЛЬ ПОВЫШЕНИЯ ЭФФЕКТИВНОСТИ ГОСУДАРСТВЕННЫХ ЗАКУПОК: ВНЕДРЕНИЕ БЕРЕЖЛИВОГО СЕРВИСА ДЛЯ ПОВЫШЕНИЯ ПРОИЗВОДИТЕЛЬНОСТИ - В.Э. Колка-Идальго; Г.В. Киспе-Сантиваньес; Д. Х. Аревало-Авесильяс; Р.А. Лучано-Алипио (Вопросы государственного и муниципального управления, 2025)
Public organisations exhibit inefficiencies in their procurement activities. These inefficiencies are the result of extended management times negatively impacting the fulfillment of established objectives.  This in turn fosters social discontent, creates inadequate work environments, and creates distrust toward the organisation.  This research proposes a model to eliminate and improve those procurement activities and processes that cause bottlenecks, that consume excessive time, and which fail to deliver value for the organisation. The objective is to strive for efficient procurement. The findings indicate that the greatest time expenditure occurs during the preparation of the “Terms of Reference” (TOR) or the “Technical Specifications” (TS). To enhance the preparation of TORs and TSs, the 5S Digital Methodology is proposed for the standardisation of documentation, and the streamlining of the procurement of goods, services, and works.A thorough review of all the activities in the phase often referred to as “Preliminary” (that is prior to the placement of the Procurement Contract) was conducted to eliminate all activities that do not add value, and/or contribute to bottlenecks and/or are counterproductive to optimisation of the time for delivery.The objective is to enhance response times in procurement, resulting in more efficient and less redundant processes. Quantitative assessment of the potential for improvement was made using the establishment of standard times were to measure workflow, then comparing them against the outcomes of previously contracted processes. The analysis revealed that over 50% of these processes consumed 300% of the standard time, highlighting a deficit that was not mapped in the organisation’s expenditures.